Training dogs to differentiate Pseudomonas aeruginosa from other cystic fibrosis bacterial pathogens: not to be sniffed at?. Issue 5 (7th November 2019) - Davies, Jane C.; Alton, Eric; Simbo, Ameze; Murphy, Ronan; Seth, Ishani; Williams, Kate; Somerville, Mark; Jolly, Libby; Morant, Steve; Guest, Claire
The major cause of lung damage in cystic fibrosis (CF) is infection with bacterial pathogens, the most prevalent of which is Pseudomonas aeruginosa, chronically infecting ∼60% patients by adolescence/adulthood (www.cysticfibrosis.org.uk/news/registry-report-2017). P.   aeruginosa may be successfully eradicated, but frequently recurs and establishes biofilms resistant to antibiotics/host defences [1]. Chronic P.   aeruginosa is closely linked with pulmonary exacerbation frequency, faster lung function decline and earlier mortality [2]. The huge antibiotic burden imposed upon patients and the resulting bacterial resistance, allergies and toxicities compound the detrimental impact of the infection itself. Chronic P.   aeruginosa should be avoided if at all possible; early detection and rapid treatment may be crucial in achieving this. Detection dogs can be trained to distinguish the major cystic fibrosis pathogen, P. aeruginosa, from a range of organisms. High sensitivity/specificity support the harnessing of this skill to detection in clinical airway samples. http://bit.ly/31GHl0Y